Kleptopia how dirty money is conquering the world - Tom, Burgis (London William Collins, 2020)
Kleptopia follows the dirty money that is flooding the global economy, emboldening dictators and poisoning democracies. From the Kremlin to Beijing, Harare to Riyadh, Paris to the Trump White House, it shows how the thieves are uniting ? and the terrible human cost.
Includes index
Keywords: Corruption